Fourth International Conference on Information Technology (ITNG'07) 2007
DOI: 10.1109/itng.2007.101
|View full text |Cite
|
Sign up to set email alerts
|

Human Computer Interaction Based Intrusion Detection

Abstract: In this paper we survey the state of the art in human computer interaction based biometrics which are based on abilities, style, preference, knowledge, or strategy used by people while working with a computer. We examine current research and analyze the types of features used to describe HCI behavior. After comparing accuracy rates for verification of users using different HCI-based biometric approaches we address privacy issues which arise with the use of HCI dependant biometrics. Finally, we present results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Gaines et al [4] studied that keystroke dynamics for each user is unique as a signature. Yampolskiy and roman [5] also confirmed that using keystroke dynamic in the authentication process can prevent intruders. Saevanee and Bhattarakosol [6] proposed a method that used keystroke dynamics combining with the finger pressure in the authentication mechanism.…”
Section: Related Workmentioning
confidence: 80%
See 1 more Smart Citation
“…Gaines et al [4] studied that keystroke dynamics for each user is unique as a signature. Yampolskiy and roman [5] also confirmed that using keystroke dynamic in the authentication process can prevent intruders. Saevanee and Bhattarakosol [6] proposed a method that used keystroke dynamics combining with the finger pressure in the authentication mechanism.…”
Section: Related Workmentioning
confidence: 80%
“…2. The keypress interval timing ratio [5] is the ratio between the interval time and the total time that used to press all passwords in each set.…”
Section: R J = [S 1 //S 2 //…//S 10 ]mentioning
confidence: 99%
“…According to [6], most common behavioral biometrics verification techniques are based on: (a) mouse dynamics, which are derived from the user-mouse interaction and are the focus of this paper; (b) keystroke dynamics, which are derived from the keyboard activity;…”
Section: Related Workmentioning
confidence: 99%
“…It also could be extended to insiders who abuse their privileges. Once firewall and the authentication level [3] are compromised, computer security falls into a serious situation. As a result, as a secondary defense line, online intrusion detection system (IDS) [4] [5] by monitoring user behavior turns to necessary.…”
Section: Introductionmentioning
confidence: 99%